2004
DOI: 10.1002/cmr.a.20009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐protonation of the pyrimidine ring: The story of a small molecule NMR problem

Abstract: ABSTRACT:This article provides a case study of a small molecule structure determination problem from the perspective of the true experience of the authors. By starting from what was intended to be a routine acylation of an aminopyrimidine derivative, we arrive, via some intriguing detours, at an unexpected carbon-protonated pyrimidine dimer. A didactic discussion is provided, which serves to highlight the way in which some puzzling questions cropped up during nuclear magnetic resonance (NMR) spectral interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We have also shown that a sterically congested 1,1-bis(pyrimidin-5-yl)-2-chloroethene-type derivative is, peculiarly, fully monoprotonated at the C(5) position and forms a stable cationic σ-complex. A detailed NMR analysis with an emphasis on the story behind our structural conclusions regarding C(5) protonation has also been given . We proposed that both steric and electronic effects might be responsible for the observed C(5) protonation, and they could account for the stability of the σ-complex in the bispyrimidine derivative.…”
Section: Introductionmentioning
confidence: 97%
“…We have also shown that a sterically congested 1,1-bis(pyrimidin-5-yl)-2-chloroethene-type derivative is, peculiarly, fully monoprotonated at the C(5) position and forms a stable cationic σ-complex. A detailed NMR analysis with an emphasis on the story behind our structural conclusions regarding C(5) protonation has also been given . We proposed that both steric and electronic effects might be responsible for the observed C(5) protonation, and they could account for the stability of the σ-complex in the bispyrimidine derivative.…”
Section: Introductionmentioning
confidence: 97%
“…For pyrimidine-metal complexes, see: Zamora et al (1997); Louloudi et al (1997); Jolibois et al (1998); Katritzky et al (1984). For carbon protonation of pyrimidines, see: Demeter & Wé ber (2004); Né meth et al (2006). For related structures, see: Hemamalini et al (2005); Krygowski et al (2005).…”
Section: Related Literaturementioning
confidence: 99%
“…However, it was recently demonstrated that carbon also can serve as an effective proton acceptor. 25,26 The need to monitor protonation of pyrimidine/purine acids or DNA/RNA prompted the development of experimental approaches, including the determination of the site of protonation or alkylation, 27,28 where UV and IR spectroscopic methods have been used widely. We also explored the use of 1 H NMR chemical shift (CS) data to determine the site of protonation by a change of CSs during titration by an acid.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, our attention was focused on heterocyclic and exocyclic nitrogen atoms and to a lesser extent on oxygen as the most probable sites of proton binding. However, it was recently demonstrated that carbon also can serve as an effective proton acceptor. , …”
Section: Introductionmentioning
confidence: 99%